2011
DOI: 10.4314/pamj.v6i1.69065
|View full text |Cite
|
Sign up to set email alerts
|

Overview of international teledermatology

Abstract: Teledermatology is essentially “dermatology at a distance”, using one of many communication technologies to expand the reach of a dermatologist to those in need of their specialized knowledge. Most international teledermatology is store-and-forward in nature, a method in which images are stored on a computer and then transmitted electronically to a consulting dermatologist. This system is more convenient and less costly than real-time teledermatology. This review will focus on several of the store-and-forward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…44 In rural provinces of Nova Scotia, Canada, in 2009, it was reported that teledermatological videoconferencing appointments decreased the scheduled waiting time duration from 13.7 weeks for face-to-face appointments to 4.6 weeks. 45 However, regarding consultation durations, a Viber-based mobile teledermatological setup in rural Nepal reported that direct consultations took 5 min, whereas teleconsultations took 12 min. 46 A randomized cluster trial evaluated this technique using a mobile phone platform in rural Mongolian clinics and it has obtained promising results: a reduction of 19,892 km in travel distance and 269 h in travel time was noted, along with a $76.36 per-patient decrease in expenses and a 75% reduction in referrals to tertiary centers.…”
Section: Waiting Period Duration Of Consultations and Travel Reductionmentioning
confidence: 99%
“…44 In rural provinces of Nova Scotia, Canada, in 2009, it was reported that teledermatological videoconferencing appointments decreased the scheduled waiting time duration from 13.7 weeks for face-to-face appointments to 4.6 weeks. 45 However, regarding consultation durations, a Viber-based mobile teledermatological setup in rural Nepal reported that direct consultations took 5 min, whereas teleconsultations took 12 min. 46 A randomized cluster trial evaluated this technique using a mobile phone platform in rural Mongolian clinics and it has obtained promising results: a reduction of 19,892 km in travel distance and 269 h in travel time was noted, along with a $76.36 per-patient decrease in expenses and a 75% reduction in referrals to tertiary centers.…”
Section: Waiting Period Duration Of Consultations and Travel Reductionmentioning
confidence: 99%
“…Teledermatology provides a new tool for monitoring skin cancer in countries such as Brazil, which has a large area and an unequal population distribution. Teledermatology essentially involves sending digital images to specialized cancer centers for evaluation by trained experts [ 8 - 10 ] and provides a platform for professional training programs and physicians to discuss complex cases without the necessity of transporting patients, which may lead to substantial savings in time and cost [ 11 ]. This approach also effectively reduces the waiting times for surgical treatment [ 12 ] and facilitates the spread of dermatological knowledge into poor regions of the world [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in information technology, medical education has relied extensively on computer‐ and internet‐based training . Dermatopathology, with its visual characteristics, is particularly suitable for such applications.…”
mentioning
confidence: 99%